Heritage Week set (Raton, NM Raton Range, 1994)
Article is about New Mexico Heritage Preservation Week and proclamation from the City of Raton.
Newspaper article + Photograph of Kathy McQueary and Joe Apache "Went to Folsom looking for a fossil skeleton"
Master list item #: 44
File location is in the Raton file Cabinet
Keywords: McQueary, Kathy; Apache, Joe -- Raton Mayor; Schwachheim, Carl; Romero, Ernesto (Mr. & Mrs.); City of Raton; Raton Museum; Historic Preservation Division; Dorsey Mansion; Capulin Volcano Visitor Center; Heritage Preservation; City Proclamations; Traveling Exhibits; Museum Exhibits; Tours; Folsom Man; Calendar of Events; Springer, New Mexico; US 64 on Highway 325 -- Capulin, New Mexico; 216 South First Street; Raton, New Mexico